2017
DOI: 10.17645/si.v5i4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Mobility-Related Economic Exclusion: Accessibility and Commuting Patterns in Industrial Zones in Turkey

Abstract: Geographers have long examined the assumption that women are locally constricted and what this means for women taking up of economic opportunities. These studies have provided valuable insights into the understanding of the spatial dimension of social exclusion. However, the investigation of the role of wider economic, physical and social contexts on women's mobility and accessibility constraints has mainly concerned the countries in North America and Western Europe. Through a mixed methods study of two indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The conclusions of the paper remained the same when the empirical analysis was conducted disregarding the qualitative match between workers' income level and educational qualification of jobs positions. Previous studies have shown that people's ability to use public transportation and hence their accessibility levels are dependent on affordability (El-Geneidy et al, 2016), disability (Casas, 2007), age (Ryan et al, 2015) or gender (Akyelken, 2017). The accessibility analysis conducted in this study did not consider these issues due to data availability constraints and is thus likely to underestimate accessibility inequalities (Neutens et al, 2010).…”
Section: Accessibility Analysismentioning
confidence: 87%
“…The conclusions of the paper remained the same when the empirical analysis was conducted disregarding the qualitative match between workers' income level and educational qualification of jobs positions. Previous studies have shown that people's ability to use public transportation and hence their accessibility levels are dependent on affordability (El-Geneidy et al, 2016), disability (Casas, 2007), age (Ryan et al, 2015) or gender (Akyelken, 2017). The accessibility analysis conducted in this study did not consider these issues due to data availability constraints and is thus likely to underestimate accessibility inequalities (Neutens et al, 2010).…”
Section: Accessibility Analysismentioning
confidence: 87%
“…The conclusions of the paper remained the same when the empirical analysis was conducted disregarding the qualitative match between workers' income level and educational qualification of jobs positions. Previous studies have shown that people's ability to use public transportation and hence their accessibility levels are dependent on affordability (El-Geneidy et al, 2016), disability (Casas, 2007), age (Ryan et al, 2015) or gender (Akyelken, 2017). The accessibility analysis conducted in this study did not consider these issues due to data availability constraints and is thus likely to underestimate accessibility inequalities (Neutens et al, 2010).…”
Section: Accessibility Analysismentioning
confidence: 91%
“…Nonetheless, different studies have shown that certain groups such as low-income families, elderly and disabled people, women and ethnic minorities often suffer disproportionately from transport disadvantages such as the lack of adequate public and private transport options and other travel difficulties related to affordability, health and safety issues (Akyelken, 2017;Lucas et al, 2016;Preston & Rajé, 2007;Sanchez et al, 2003). These disadvantages are particularly acute in low-income and marginalized areas, where poor transport combined with the lack of economic opportunities and basic services can potentially lead to spatial poverty traps and deepen socio-spatial inequalities (Cervero et al, 2002;Lucas et al, 2016;Porter, 2014).…”
Section: List Ofmentioning
confidence: 99%
“…While the idea of equity always implies a moral judgement, equality does not have to imply a normative stance if the term is used in a descriptive sense to indicate full equality or sameness (van Wee & Geurs, 2011). The studies in transportation equity generally look at differences in the levels of accessibility to opportunities or daily travel behavior patterns of various social groups as proxies to reflect different levels of well-being or how those groups are more or less integrated into society (Akyelken, 2017;Fransen et al, 2018;Vasconcellos, 2005).…”
Section: Nexus Of Justice and Transportationmentioning
confidence: 99%
See 1 more Smart Citation